Unweaving the Web Deception and Adaptation in Future Urban Operations - Gerwehr, Scott (RAND Corporation, 2002)
Deception is a powerful yet understudied instrument of war. Using the extensive literature on deception in the animal kingdom, where ruses of near-infinite variety are applied to offense, defense, and intelligence gathering, the authors delve into the theory of deception to reveal new avenues of experimentation. These pathways may lead to new technologies or training techniques and provoke a new look at deception doctrine applicable at every level of war. ISBN: 0-8330-3159-7 Price: $24.00 Page count: 98